Situation Report: Poland, 21 September 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Cardinal Glemp Addresses Farmers in Czestochowa / by Ewa Celt The Anniversary of the August 1980 Gdansk Agreement / by Anna Swidlicka The Case of Grzegorz Przemyk / by Anna Swidlicka Poverty Increasing The Ponal Dispute: A Storm in the Vodka Glass / by Ewa Celt